2006
DOI: 10.1063/1.2207721
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence properties of CdTe∕CdSe core-shell type-II quantum dots

Abstract: We report investigations on the optical properties of type-II CdTe∕CdSe core-shell quantum dots. By varying the core size, we provide an elegant way to verify that the detected emission signal indeed arises from type-II band alignment. The photoluminescence (PL) peak energy increases with a third root of the excitation power. Both of the PL peak energy and linewidth exhibit unique temperature dependence. All these observations can be rationalized by the band bending effect resulting from the spatially separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 16 publications
7
38
0
Order By: Relevance
“…8(b and c) shows the dependences of the PL-peak energy (E peak ) on a cubic root of P ex (denoted as P 1/3 ex ). It comes to our attention that these dependences are linear, which is a typical token usually found in type-II heterostructures [14,35,45]. However, if observing carefully the P 1/3 ex dependences of E peak , one can see that the slope of the linear lines is quite small.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…8(b and c) shows the dependences of the PL-peak energy (E peak ) on a cubic root of P ex (denoted as P 1/3 ex ). It comes to our attention that these dependences are linear, which is a typical token usually found in type-II heterostructures [14,35,45]. However, if observing carefully the P 1/3 ex dependences of E peak , one can see that the slope of the linear lines is quite small.…”
Section: Resultsmentioning
confidence: 91%
“…By engineering semiconductors with suitable band-gap energies and band alignment, one can produce indirectly excitonic emissions as expected. Type-II core/shell materials have been widely studied to be known as Cu 2 S/CdS [21], CdTe/CdSe [1,[33][34][35], (Zn,Cd)Te/CdSe [18,36], CdSe/ZnTe [33], CdTe/ZnSe [37], CdTe/CdS [38], (ZnSe/CdS)/CdS [16], ZnSe/CdS/ZnSe [12], and ZnSe/CdS (or CdS/ZnSe) [2,4,5,19,20,22]. Besides the type-I (or inverse type-I) and type-II core/shell heterostructures, it has been also introduced quasi-type-II (equivalent to type-I 1/2 ) core/shell structures with many intriguing optical properties [17,18,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In superlattices, however, the coupling between the quantum wells tends to reduce the charge localization and separation as shown by the probability densities in Fig. 2(b).…”
Section: à3mentioning
confidence: 99%
“…While the ZnSe/ZnTe system has been intensively investigated, 9,10 little work has so far been done for the CdSe/CdTe system. [11][12][13] In particular, there was no experimental papers reporting the properties of CdSe/CdTe superlattices or the valence band offset between CdSe and CdTe. In order to address these issues, this work reports the growth and the structural and optical characterization of a series of CdSe/CdTe superlattices.…”
mentioning
confidence: 99%
“…2(b) demonstrates very-high crystalline-quality at the atomic length scale. It has been reported that the unstrained CdTe and CdSe forms a type-II band edge alignment 11,12 with the respective bandgap energies 1.76 eV (Refs. 12 and 20) and 1.61 eV (Refs.…”
mentioning
confidence: 99%